(untitled) (Indian Journal of Veterinary Pathology, 2025)
Foot and mouth disease (FMD) is a contagious viral disease that has a high economic impact on livestock industry affecting large and small ruminant. Most research works are carried out on hematobiochemical alteration due to FMD virus (FMDV) in bovine but there is a paucity of literature and a dearth of research on how FMDV affects the hematobiochemical profiles of goats. This study was aimed to investigate the impact of FMDV on hematobiochemical profile of goats. Forty two whole blood samples were collected from FMDV-infected (n=32) and apparently healthy (n=10) goats to estimate hematobiochemical profile alteration. There was a significant (p<01) decrease in values of hematobiochemical parameters viz. haemoglobin (6.45±0.55 g%), total erythrocytes (4.22±0.27x106/µl), packed cell volume (21.35±1.66%), mean corpuscular volume (50.49±0.65 fl), mean corpuscular haemoglobin (15.24±0.32 pg), mean corpuscular haemoglobin concentration (30.19±0.25 gm/dl), glucose (20.42±4.24 mg/dL), alanine transaminase (29.26±3.74 U/L), blood urea nitrogen (39.57±4.46 mg/dL), serum creatinine (0.7±0.12 mg/dL), sodium ion (143.73±1.33 mEq/L), total protein (7.57±0.55 g/dL), albumin (3.15±0.31 g/dL), globulin (4.425±0.37 g/dL). There was a significant (p<01) increase of aspartate transaminase (86.36±11.41 U/L), albumin: globulin ratio (0.715±0.08) as well as cholesterol (104.77±0.86 mg/dL) and no significant changes were observed in alkaline phosphatase (267.76±236.52 U/L), potassium ion (5.21±0.36 mEq/L), neutrophils, monocytes, lymphocytes, eosinophils in FMDV infected goats than the apparently healthy goat. Hematobiochemical parameters alter significantly in goat during the active phase of FMDV infection under natural condition and these findings would be useful for developing a therapeutic or preventive measure to avoid the biotic stress and negative effect of FMD virus infection in convalescent goat.